"African Elephant Specialist Group report/Rapport du Groupe des Specialistes des Elephants d""Afrique" - Dublin, Holly (Pachyderm, 2001)
Besides programme review information, which includes the installation of a Programme Officer for the Central African Region, ongoing work on MIKE, ETIS, reintroduction guidelines, the AfESG website, and AED update, the report mentions the recent evidence on the existence of two subspecies of African elephants, and the implications this taxonomic distinction may bring to the debate and conservation/management of elephants on the continent.